2016
DOI: 10.1107/s2053273315022457
|View full text |Cite
|
Sign up to set email alerts
|

Towards solution and refinement of organic crystal structures by fitting to the atomic pair distribution function

Abstract: A method towards the solution and refinement of organic crystal structures by fitting to the atomic pair distribution function (PDF) is developed. Approximate lattice parameters and molecular geometry must be given as input. The molecule is generally treated as a rigid body. The positions and orientations of the molecules inside the unit cell are optimized starting from random values. The PDF is obtained from carefully measured X-ray powder diffraction data. The method resembles `real-space' methods for struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 39 publications
0
27
0
2
Order By: Relevance
“…R PDF values cannot be compared with R values from single-crystal or Rietveld refinements. In our experience a R wp PDF value of 30-40% for an organic compound denotes a reasonable fit (Prill et al, 2016). It is remarkable that some of the models gave a very good fit to the PDF data [e.g.…”
Section: Crystal Structure Refinement By Fit To the Pdf Datamentioning
confidence: 57%
See 2 more Smart Citations
“…R PDF values cannot be compared with R values from single-crystal or Rietveld refinements. In our experience a R wp PDF value of 30-40% for an organic compound denotes a reasonable fit (Prill et al, 2016). It is remarkable that some of the models gave a very good fit to the PDF data [e.g.…”
Section: Crystal Structure Refinement By Fit To the Pdf Datamentioning
confidence: 57%
“…The structures match very well. Obviously, the geometrical accuracy of the structure from the PDF fit is quite high, as was already observed by Prill et al (2016). In contrast, the structural model G [ Fig.…”
Section: Tablementioning
confidence: 74%
See 1 more Smart Citation
“…It has recently been shown that the application of a pair distribution function, PDF, transformation to synchrotron XRPD data can be used to extract structural information from nanocrystalline samples of organic compounds which do not give Bragg diffraction (Prill et al, 2016). Below the structure determination level, the application of a PDF transform to XRPD data obtained using copper-based laboratory X-ray equipment improves the classification of amorphous samples and the principal component analysis, PCA, of sample processing history (Nollenberger et al, 2009;Boetker et al, 2012).…”
Section: Pair Distribution Function Transformation Of Xrpd Data Usingmentioning
confidence: 99%
“…) which are the building blocks of organic compounds. The atomic pair distribution function (PDF) calculated from X-ray (and/or neutron, electron) total scattering has been demonstrated to be a valuable tool for investigating structures of disordered and amorphous organic compounds (Shi et al, 2017;Prill et al, 2015Prill et al, , 2016Benmore & Weber, 2011;Rademacher et al, 2012;Chen et al, 2014;Gorelik et al, 2015). Although existing tools such as DiffPy-CMI (Juhá s et al, 2015) and XISF (Mou et al, 2015) can be used for this problem, a new software program that provides a user-friendly graphical user interface (GUI, as opposed to script-based programming in DiffPy-CMI) and analyzes the data in real space (as opposed to in reciprocal space in XISF) is still of great value.…”
Section: The Crystallographic Problemmentioning
confidence: 99%